Causes of Migration of Menonitas in the World, Canada and México: ¿Was their Mobility a Success or a Failure? (Revista LIDER, 2014)
The Menonita movement has been characterized by its mobility andresilience. This study investigates the causes that explain the above, withsupport of literature on the subject and primary sources. It concludes that this minority has been able to preserve its character in relation to its confession, ideology and modus vivendi.